An analysis of educational faculty students’ research self-efficacy in terms of a number of variables - Saral, Duygu Gizem; ÖZDOĞAN, DİDEM (Elsevier, 2015)
Enabling students to acquire the research abilities is an educational issue. The target of education is to raise individuals with research-oriented attitudes and behaviours. Sustaining the research activities requires that, in addition to the compatibility of research environments, individuals and institutions to conduct the research have the competence facilitating them to do the research. Therefore, the need was felt to determine educational faculty students’ levels of research self-efficacy. This research examines whether or not educational faculty students’ research self-efficacy differs on the basis of gender, university, department, and taking or not taking the Scientific Research Methods course. The research sample was composed of 532 volunteering students attending the Psychological Counseling and Guidance, Elementary School Mathematics Teaching, Science Teaching, and Computer and Teaching Technologies departments of the educational faculties of Amasya and Eskişehir Osmangazi Universities. The research data were obtained through a 43-item, 5-pointed Likert scale of Research Competence (Büyüköztürk, 1997), with a reliability coefficient of α=0,89 . In the analysis of the data, the frequencies and the percentages for the variables were calculated, the one-way variance analysis (ANOVA) and the significance test for the difference between two averages (the t-test) were employed. When differences were found between the groups in consequence of the variance analysis, between which groups the differences were available was found via the Scheffe test. Consequently, it was found that educational faculty students’ research self-efficacy differed according to department, and to whether they took the Scientific Research Methods course; but that it did not differ according to gender or university.
Keywords: research; self-efficacy